Istirātījiyyah Ta’bīr al-Ṣuwar fī Mahārah al-Kalām - Fazira, Era; Ahkas, Akmal Walad (Study Program of Arabic Language Teaching, 2025)
This study aims to analyze the effectiveness of the Picture Description strategy in improving speaking skills among seventh-grade students at Al-Durrah Integrated Private Islamic Secondary School in Mariela. The study employed a qualitative approach using a case study method. Data were collected through classroom observations, interviews with the Arabic language teacher and five students, questionnaires administered to all students, and documents such as pictures of learning activities, lesson plans, and students’ work. The data were analyzed through data reduction, data display, and verification in a narrative form. The results showed that applying the “Picture Description” strategy increased student engagement, self-confidence, and ability to construct meaningful and contextual oral sentences. Visual media also helped students understand vocabulary and express their ideas more confidently. Moreover, this strategy effectively overcame the traditional Arabic instruction's negative and monotonous nature. The significance of this study lies in its provision of the first empirical evidence at the middle school level regarding the effectiveness of the “Picture Description” strategy. It also offers practical contributions to Arabic language teachers in designing more communicative and contextualized instruction that aligns with the needs of 21st-century learners.